Additions to the Indonesian fauna of the hermit crab genus Pseudopaguristes McLaughlin and a further division of the genus Paguristes Dana (Crustacea: Decapoda: Paguroidea: Diogenidae) - Rahayu, Dwi Listyo (Zootaxa, 2005)
An in-depth study of the genera Paguristes Dana, 1851 and Pseudopaguristes McLaughlin, 2002 in Indonesian waters has resulted in refined hypotheses of some of the evolutionary trajectories within the Paguroidea. Not only has the observed reduction in pleurobranch and arthrobranch number in three species, Paguristes hians Henderson, 1888, P. kuekenthali De Man, 1902 and P. monoporus Morgan, 1987 required the transfer of these taxa to Pseudopaguristes, they, and two new species, have required an emendation of the genus itself. Additionally, the investigation has also revealed anintermediate evolutionary change that heretofore has gone unrecognized. In several, apparently less derived, representatives of Paguristes, the characteristic gill number of 13 pairs (ten of arthrobranchs and three pleurobranchs) has been reduced to 12, with the loss of the pleurobranch on the wall of fifth thoracic somite. Only one of these recognized species, Paguristes tuberculatus Whitelegge, 1900, occurs in Indonesian waters. The genus Stratiotes, Thomson, 1899, erected for Pagurus setosus Filhol, 1885, a junior synonym of Paguristes setosus (H. Milne Edwards, 1848), is reinstated because its type species has proved to have 12 pairs of gills. Three new species are included in Stratiotes: S. micheleae n. sp., S. breviantennatus n. sp., and S. ngochoae n. sp. The new species assigned to Pseudopaguristes are P. asper n. sp. and P. gracilis n. sp.